DOI: 10.7190/shu-thesis-00191
|View full text |Cite
|
Sign up to set email alerts
|

Auxetic foams for sports applications

Abstract: Bell helped extend the research techniques surrounding polymer chemistry. Advice, support and equipment access was provided by Jamie Boulding who operates the Instron devices and ovens used for foam conversion at Sheffield Hallam. Help was also provided in the engineering workshops by Tim O'Hara, Will Tierney, Robin Sykes, Jeremy Bladen and Simon Apps. Terry Senior from the Centre of Sports Engineering Research helped with the design of moulds and experiments, and the whole of the Equipment Mechanics Research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…In this regard, auxetic foam shows great promise on this front owing to its superior energy absorption capabilities [201]. In a recent study, Duncan [202] suggested the use of auxetic foam structures in the production of personal protection equipment (PPE) for sports personnel with higher mechanical and impact properties. Some of the potential equipment includes cricket pads, shin pads, crash helmets, and car bumpers.…”
Section: Applicationsmentioning
confidence: 99%
“…In this regard, auxetic foam shows great promise on this front owing to its superior energy absorption capabilities [201]. In a recent study, Duncan [202] suggested the use of auxetic foam structures in the production of personal protection equipment (PPE) for sports personnel with higher mechanical and impact properties. Some of the potential equipment includes cricket pads, shin pads, crash helmets, and car bumpers.…”
Section: Applicationsmentioning
confidence: 99%
“…One can mention here, for example, the following applications of auxetics: medical and biomedical applications (e.g., stents, dilators for opening the cavity of an artery, coronary angioplasty and related procedures, smart bandages, smart filters); sports applications (sport helmets, protection against extreme weather during outdoor/adventure sports), molecular sieves and filters and defouling applications; displacement amplifiers; auxetic cushions in seats; auxetic springs; acoustic-to-electrical energy conversion; electromagnetic applications in antennas and reflectors; applications in fabrics, garments, and fashion apparel; fabrication of 3D auxetic fabric; auxetic shape memory alloys; footwear and articles of apparel; etc. One can find more details about applications of auxetic materials and structures in previous articles [7][8][9][41][42][43].…”
Section: Introductionmentioning
confidence: 99%